Flotation Performance and Gas Dispersion Properties in a Laboratory Flotation Cell - Maldonado-Saavedra, M; Miranda-Moreno, N; Femenias-Castro, F (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Flotation is a complex process that exhibits high dimensionality which makes modeling and optimization very challenging. One technique to alleviate the dimensionality problem is to combine variables together into more informative ones. Bubble surface area flux and air recovery are examples of dimensionality reduction. Gas holdup also captures the effect of a plurality of variables including gas rate, bubble size, surfactant type, and concentration. This work makes use of a dual flotation–conductivity cell to explore the relationship between gas dispersion properties, including frother concentration and flotation performance. Results demonstrate that gas holdup effectively captured the effect of gas rate and frother concentration and better correlates to flotation performance. © 2022 by the authors.